Clinical-pathological features and perioperative outcomes of mediastinoscopy vs. thoracoscopy esophagectomy in esophageal cancer: A meta-analysis - Gong, Sheng; Rao, Xin; Yuan, Ye; Yao, Xiaojun; Li, Gang; Wang, Ning; Li, Dan; Jiang, Liangshuang (Frontiers in Surgery, 2023)
Objective: To compare the clinicopathological features and perioperative outcomes of video-assisted mediastinoscopy esophagectomy (VAME) compared to video-assisted thoracoscopy esophagectomy (VATE) in esophageal cancer. Methods: We comprehensively searched online databases (PubMed, Embase, Web of Science and Wiley online library) to find available studies exploring the clinicopathological features and perioperative outcomes between VAME and VATE in esophageal cancer. Relative risk (RR) with 95% confidence interval (CI) and standardized mean difference (SMD) with 95% CI were used to evaluate the perioperative outcomes and clinicopathological features. Results: A total of seven observational studies and one randomized controlled trial involving 733 patients were considered eligible for this meta-analysis, of which 350 patients underwent VAME in contrast to 383 patients underwent VATE. Patients in the VAME group had more pulmonary comorbidities (RR = 2.18, 95% CI 1.37 – 3.46, P = 0.001). The pooled results showed that VAME shortened the operation time (SMD = -1.53, 95% CI - 2.308 – -0.76, P = 0.000), and retrieving less total lymph nodes (SMD = -0.70, 95% CI -0.90 – -0.50, P = 0.000). No differences were observed in other clinicopathological features, postoperative morbidities or mortality. Conclusions: This meta-analysis revealed that patients in the VAME group had more pulmonary disease before surgery. The VAME approach significantly shortened the operation time and retrieved less total lymph nodes and did not increase intra- or postoperative complications.